Graduated compression stockings for prevention of deep vein thrombosis - Sachdeva, Ashwin; Dalton, Mark; Lees, Timothy (The Cochrane Database of Systematic Reviews, 2018)
Graduated compression stockings for prevention of deep vein thrombosis during a hospital stay , Background , Deep vein thrombosis (DVT) is a blood clot that forms in a vein deep in the body, usually in the leg or pelvic veins. A number of factors such as reduced mobility, older age, obesity, active cancer, major surgery, major injuries, history of previous DVT, family history of DVT, and recent period of illness may increase the risk of developing a DVT. Hospital patients, who often have one or more of these risk factors, are at particular risk of developing DVT, either immediately after surgery or if they are immobile due to a medical illness., Symptoms of DVT vary from none to pain and swelling in the legs. A blood clot can move from the leg to the lungs, with the danger of pulmonary embolism (PE) and death. The main treatment for DVT includes the use of blood‐thinning drugs (anticoagulation). Deep vein thrombosis usually resolves, but it can have long‐term effects such as high venous pressure in the leg, leg pain, swelling, darkening of the skin, and inflammation., Deep vein thrombosis can be prevented with the use of compression or drugs. Drugs can cause bleeding, which is a particular concern in surgical patients. Graduated compression stockings (GCS) help prevent the formation of blood clots in the legs by applying varying amounts of pressure to different parts of the leg., Study characteristics and key results , We identified 20 randomised controlled trials (studies in which participants are assigned to a treatment group using a random method) (2853 analytic units consisting of 1681 individual patients and 1172 individual legs) in our most recent search on 12 June 2018. Nine trials compared wearing stockings to no stockings, and 11 compared stockings plus another method with that method alone. The other methods used were dextran 70, aspirin, heparin, and mechanical sequential compression. Of the 20 trials, 10 included patients undergoing general surgery; six included patients undergoing orthopaedic surgery; three individual trials included patients undergoing neurosurgery, cardiac surgery, and gynaecological surgery, respectively; and only one trial included medical patients (patients who were admitted to the hospital for reasons other than surgery). The compression stockings were applied on the day before surgery or on the day of surgery and were worn up until discharge or until the patients were fully mobile. Thigh‐length stockings were used in the vast majority of included studies. The included studies were of good quality overall. We found that wearing GCS reduced the overall risk of developing DVT, and probably also DVT in the thighs. We found that GCS may also reduce the risk of PE amongst patients undergoing surgery. As only one trial included medical patients, results for this population are limited. The occurrence of problems associated with wearing GCS was poorly reported in the included studies., Quality of the evidence , Our review confirmed that GCS are effective in reducing the risk of DVT in hospitalised surgical patients (high‐quality evidence). It also demonstrated that GCS probably reduce the risk of developing DVT in the thighs (proximal DVT, moderate‐quality evidence) and PE (low‐quality evidence). Reasons for downgrading the quality of the evidence included low event rate (i.e. small number of participants who developed DVT) and uncertainty due to only a small number of patients being routinely screened for proximal DVT or PE. Limited evidence was available for hospitalised medical patients, with only one study suggesting that GCS may prevent DVT in such patients.